(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Ethical considerations play a fundamental role in shaping the practices and interactions within the dental profession. This article examines the ethical responsibilities of both dentists and dental assistants, highlighting the principles that guide their conduct and decision-making in patient care. Dentists are entrusted with upholding patient autonomy, promoting beneficence and non-maleficence, advocating for justice, and maintaining professional integrity. Similarly, dental assistants bear ethical responsibilities, including safeguarding patient confidentiality, establishing professional boundaries, pursuing competence, advocating for patients’ rights, and engaging in ethical decision-making. By adhering to these ethical standards, dentists and dental assistants contribute to the delivery of high-quality dental care while fostering trust, integrity, and patient-centered practice.